Intenção e Conciliação de Metas (PERcursos Linguísticos, 2020)
I analyze in this study potentialities of modeling communicative interactions assuming one can conceive processes of ostensive communication as converting practical intentions into informative and communicative intentions. So, one can only achieve collaboratively a practical intention through the recognition the speaker intends to make mutually manifest or more manifest certain set of assumptions by overtly or communicative ostensible stimuli. Firstly, I present the goal-conciliation abductive-deductive architecture in the case of self-conciliation, then I discuss a case of collaborative heteroconciliation, and finally, I draw some considerations about intention in the light of an approach to communication as a proactive agency.